Q:

PLEASE HELP ASAP 40 PTS + BRAINLIEST TO RIGHT/BEST ANSWER Zoom in a bit, the answers are a tad glitched ):

Accepted Solution

A:
Answer:see explanationStep-by-step explanation:Using the coefficients of the polynomial and evaluating for h = - 3 - 3 | 1   - 4   - 9   36       ↓   - 3   21   - 36       -------------------------        1   - 7   12   0 ← remainderSince remainder is 0 then (x + 3) is a factor, soy = (x + 3)(x² - 7x + 12)To factor the quadraticConsider the factors of the constant term (+ 12) which sum to give the coefficient of the x- term (- 7)The factors are - 4 and - 3, since- 4 × - 3 = + 12 and - 4 - 3 = - 7, thenx² - 7x + 12 = (x - 4)(x - 3), andy = (x + 3)(x - 4)(x - 3)